Zinc sulfide / titanium dioxide heterojunction nano material and preparation and application thereof

By growing ZnS on the surface of TiO2 by a one-step hydrothermal method, a controllable zinc sulfide/titanium dioxide heterojunction nanomaterial was constructed, which solved the problems of complex process, low reproducibility and difficulty in controlling ZnS load in the existing technology, and realized industrialization Efficient production and efficient catalytic performance.

CN119425728APending Publication Date: 2025-02-14DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310965917.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-02
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

When constructing a zinc sulfide/titanium dioxide heterojunction, the process is complex, the reproducibility is not high, and the load control of ZnS is difficult, and the applicable scenarios are narrow, making it difficult to achieve industrial and efficient production.

Method used

ZnS is directly grown on the surface of TiO2 by one-step hydrothermal method, and a heterojunction structure with controllable proportions and controllable ZnS morphology is constructed. By placing the precursor of TiO2, zinc, sodium chloride and/or potassium chloride in the solvent After stirring evenly, adding sulfur precursor, solvent heat treatment was performed, followed by washing and drying to obtain zinc sulfide/titanium dioxide heterojunction nanomaterial.

Benefits of technology

The zinc sulfide/titanium dioxide heterojunction nanomaterial is achieved with simple controllability, good reproducibility, low cost, and is suitable for industrial and efficient production. The material exhibits efficient catalytic performance in the fields of photocatalysis, thermal catalysis and electrocatalysis.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0004373521850000011
    Figure HDA0004373521850000011
Patent Text Reader

Abstract

The invention discloses a preparation method of a zinc sulfide / titanium dioxide heterojunction nano material, and belongs to the field of nano catalytic materials. Titanium dioxide, a precursor of zinc, a precursor of sulfur, sodium chloride and / or potassium chloride are fully and uniformly stirred in a solution, then solvent heat treatment is performed, and after cooling, the zinc sulfide / titanium dioxide heterojunction nano material is obtained through ethanol and water washing. The method has the advantages of being simple, controllable, good in reproducibility, low in cost, suitable for industrial efficient production and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of nano-catalytic material preparation, and in particular to a method for preparing a zinc sulfide / titanium dioxide heterojunction nano-material. Background Art

[0002] TiO2 is a green, clean, stable, low-cost, and widely used multiphase photocatalytic material. However, due to its narrow bandgap, it leads to a high degree of recombination of photogenerated electrons and holes and low photon utilization. It is usually improved by doping, loading metal or non-metal additives, and building heterojunctions. ZnS is also a catalyst that absorbs ultraviolet light. Since its Fermi level and vacuum level are significantly different from those of TiO2, which can be simply understood as the difference in its absorption band edge, it can enhance the separation of photogenerated carriers with TiO2 by building a heterojunction. At the same time, the redox sites on the surfaces of ZnS and TiO2 can be further used in CO2 reduction, H2O2 preparation, hydrogen production and other application fields.

[0003] The current methods for constructing zinc sulfide / titanium dioxide heterojunctions include gel method, electrochemical deposition, colloidal deposition, hydrothermal method and other methods. Limited by the complex processes and low reproducibility of the previous methods, the hydrothermal method is a relatively simple preparation strategy. The currently reported hydrothermal method uses electrospinning to prepare TiO2 nanofibers, and then hydrothermally grows ZnS in one step to construct an S-type heterojunction (Yao Rongsu et al., doi: 10.1002 / adsu.202200027). It is applicable to a narrow range of TiO2 scenarios, and the ZnS loading can only be controlled at 2-10wt%.

[0004] Therefore, there is an urgent need to develop a one-step hydrothermal strategy with wide applicability, a large adjustable ZnS loading range, simple process, and suitability for industrial and efficient production. Summary of the invention

[0005] The object of the present invention is to provide a method for preparing a zinc sulfide / titanium dioxide heterojunction nanomaterial, which has the advantages of being simple and controllable, having good reproducibility, low cost, and being suitable for industrialized and efficient production.

[0006] A method for preparing a zinc sulfide / titanium dioxide heterojunction nanomaterial, the method comprising:

[0007] (1) TiO2, zinc precursor, and sodium chloride and / or potassium chloride are stirred uniformly in a solvent, and then a sulfur precursor is added and stirred uniformly;

[0008] (2) transferring the mixed slurry to a reactor for solvent thermal treatment;

[0009] (3) After cooling, the solid part is washed with ethanol and water in sequence, separated by centrifugation, and dried to obtain zinc sulfide / titanium dioxide heterojunction nanomaterials.

[0010] Preferably, the TiO2 in step (1) is anatase phase and / or rutile phase; the morphology of TiO2 is one or more of controllably synthesized morphologies such as one-dimensional nanofibers, two-dimensional nanosheets and nanotubes, three-dimensional nanoparticles and nanorods; the zinc precursor is one or more of zinc sulfate, zinc nitrate and zinc chloride; the sulfur precursor is L-cysteine, thiourea and thioacetamide; the solvent is one or more of water, ethanol, ethylene glycol and isopropanol; the molar ratio of the zinc precursor to the sulfur precursor is 1:1 to 1:5, preferably 1: 1~1:2; the molar ratio of the zinc precursor and sodium chloride or potassium chloride is 4:1~1:1, preferably 2:1~4:3; the mass ratio of TiO2 and the zinc-based precursor to form ZnS is 0.001~1000:1, preferably 0.01~100:1; the ratio of the volume of the solvent to the mass of the material (the sum of TiO2, zinc precursor, sulfur precursor, and sodium chloride and / or potassium chloride) is 10~50mL / g, preferably 15~30mL / g; the two stirring times are both 0.5~2h, preferably 0.5~0.8h.

[0011] Preferably, in step (2), the solvent thermal treatment is carried out in a sealed reactor, the temperature of the solvent thermal treatment is 120-200° C., preferably 120-150° C.; the time of the solvent thermal treatment is 12-48 h, preferably 16-24 h.

[0012] Preferably, the amount of ethanol and water used to alternately wash the solid part in step (3) is 200-800 mg solid / 25 mL (ethanol or water), for a total of 3-8 times; the vacuum drying temperature is 60-100° C., preferably 70-80° C.; and the drying time is 12-36 h, preferably 18-24 h.

[0013] The present invention constructs a heterojunction structure with controllable proportion and ZnS morphology by directly growing ZnS on the TiO2 surface by a one-step hydrothermal method. In the field of photocatalysis, it can effectively promote the separation of photogenerated electron-hole pairs and promote the efficient progress of the reaction; in the field of thermal catalysis, it can use and regulate the surface Lewis acidity / Lewis basicity of different compositions for catalytic conversion research; in the field of electrocatalysis, this strategy can be used to modify the electrode to enhance the electron transmission and catalytic performance between it and the reactant.

[0014] Compared with the prior art, the present invention has the following unique advantages:

[0015] (1) The present invention directly grows ZnS on the TiO2 surface through a one-step hydrothermal method to construct a heterojunction structure with controllable proportion and ZnS morphology.

[0016] (2) The zinc sulfide / titanium dioxide heterojunction described in the present invention is a multiphase catalytic material, which can be applied to processes such as photolysis of water to produce hydrogen, and can be recovered and recycled.

[0017] (3) The preparation method of the zinc sulfide / titanium dioxide heterojunction nanomaterial described in the present invention is simple and controllable, has good reproducibility, low cost, and is suitable for industrial and efficient production. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 This is the XRD pattern of TiO2 / ZnS-20 obtained in Example 1. DETAILED DESCRIPTION

[0019] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention clearer and more understandable, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and do not limit the scope of the present invention. The experimental schemes in the following embodiments that do not specify specific conditions are usually carried out under conventional conditions or under conditions recommended by the manufacturer.

[0020] Example 1

[0021] The zinc sulfide / titanium dioxide heterojunction with a TiO2 mass fraction of 20% was obtained by the following process: First, 4.0mmol zinc sulfate, 3.0mmol sodium chloride and TiO2 nanoparticles (anatase phase) with a ZnS mass fraction of 20% were added to 30mL ethanol solution and stirred for 0.5h. Then 8.0mmol thioacetamide was added and stirred for 0.5h and then transferred to a Teflon reactor lined with polytetrafluoroethylene, sealed and heat treated at 160℃ for 20h. After cooling to room temperature, the solid part was washed alternately with ethanol (25mL / time) and water (25mL / time) and centrifuged for 6 times. Finally, it was vacuum dried at 60℃ for 18h, cooled to room temperature, and ground to obtain a zinc sulfide / titanium dioxide heterojunction nanomaterial with a TiO2 mass fraction of 20%, with a particle size of 10-100nm, marked as TiO2 / ZnS-20.

[0022] XRD test confirmed ( Figure 1 ), the crystalline phase of TiO2 in the prepared zinc sulfide / titanium dioxide heterojunction with a TiO2 mass fraction of 20% is anatase phase, and the crystalline phase of ZnS is sphalerite phase, and the zinc sulfide / titanium dioxide heterojunction nanomaterial is successfully prepared.

[0023] The reaction evaluation is shown in Application Example 1 and Comparative Example 1.

[0024] Example 2

[0025] The zinc sulfide / titanium dioxide heterojunction with a TiO2 mass fraction of 10% was obtained by the following process: First, 4.0mmol zinc sulfate, 3.0mmol potassium chloride and TiO2 nanoparticles (rutile phase) with a ZnS mass fraction of 10% were added to 30mL ethylene glycol solution and stirred for 1.0h. Then, 8.0mmol thioacetamide was added and stirred for 1.0h and then transferred to a Teflon reactor lined with polytetrafluoroethylene, sealed and heat treated at 160℃ for 20h. After cooling to room temperature, the solid part was washed alternately with ethanol (25mL / time) and water (25mL / time) and centrifuged for 6 times. Finally, it was vacuum dried at 60℃ for 24h, cooled to room temperature, and ground to obtain a zinc sulfide / titanium dioxide heterojunction nanomaterial with a TiO2 mass fraction of 10%, with a particle size of 10 to 100nm, marked as TiO2 / ZnS-10.

[0026] XRD test confirmed that the crystal phase of TiO2 in the prepared zinc sulfide / titanium dioxide heterojunction with a TiO2 mass fraction of 10% was rutile phase, and the crystal phase of ZnS was sphalerite phase, and the zinc sulfide / titanium dioxide heterojunction nanomaterial was successfully prepared.

[0027] Reaction Evaluation Reference Application Example 1 (the difference is that the Ba prepared in Example 1 2.0 -Bi4Ti3O 12 The catalyst was replaced by the catalyst prepared in this example of equal mass), and the hydrogen yield was 94.1 μmol g -1 h -1 , compared with comparative example 1, the hydrogen yield increased by about 4 times, indicating that TiO2 / ZnS-10 was successfully prepared.

[0028] Example 3

[0029] The zinc sulfide / titanium dioxide heterojunction with a TiO2 mass fraction of 5% was obtained by the following process: First, 4.0mmol zinc nitrate, 3.0mmol sodium chloride and TiO2 nanoparticles (anatase phase) with a mass fraction of 5% ZnS were added to 30mL ethanol solution and stirred for 1.0h. Then 8.0mmol thiourea was added and stirred for 1.0h and then transferred to a Teflon reactor lined with polytetrafluoroethylene, sealed and heat treated at 180℃ for 20h. After cooling to room temperature, the solid part was washed alternately with ethanol (25mL / time) and water (25mL / time) and centrifuged for 6 times. Finally, it was vacuum dried at 60℃ for 18h, cooled to room temperature, and ground to obtain a zinc sulfide / titanium dioxide heterojunction nanomaterial with a TiO2 mass fraction of 5%, with a particle size of 10-100nm, marked as TiO2 / ZnS-5.

[0030] XRD test confirmed that the crystal phase of TiO2 in the prepared zinc sulfide / titanium dioxide heterojunction with a TiO2 mass fraction of 5% was anatase phase, and the crystal phase of ZnS was sphalerite phase, and the zinc sulfide / titanium dioxide heterojunction nanomaterial was successfully prepared.

[0031] Reaction Evaluation Reference Application Example 1 (the difference is that the Ba prepared in Example 1 2.0 -Bi4Ti3O 12 The catalyst was replaced by the catalyst prepared in this example of equal mass), and the hydrogen yield was 136.9 μmol g -1 h -1 , compared with comparative example 1, the hydrogen yield increased by about 5 times, indicating that TiO2 / ZnS-5 was successfully prepared.

[0032] Example 4

[0033] The zinc sulfide / titanium dioxide heterojunction with a TiO2 mass fraction of 50% was obtained by the following process: First, 4.0mmol zinc chloride, 3.0mmol sodium chloride and TiO2 nanoparticles (anatase phase) with a mass fraction of 50% ZnS were added to 30mL aqueous solution and stirred for 0.5h. Then 8.0mmol L-cysteine ​​was added and stirred for 0.5h and then transferred to a Teflon reactor lined with polytetrafluoroethylene, sealed and heat treated at 150℃ for 24h. After cooling to room temperature, the solid part was washed alternately with ethanol (25mL / time) and water (25mL / water) and centrifuged for 6 times. Finally, it was vacuum dried at 80℃ for 18h, cooled to room temperature, and ground to obtain a zinc sulfide / titanium dioxide heterojunction nanomaterial with a TiO2 mass fraction of 50%, with a particle size of 10-100nm, marked as TiO2 / ZnS-50.

[0034] XRD test confirmed that the crystal phase of TiO2 in the prepared zinc sulfide / titanium dioxide heterojunction with a TiO2 mass fraction of 50% was anatase phase, and the crystal phase of ZnS was sphalerite phase, and the zinc sulfide / titanium dioxide heterojunction nanomaterial was successfully prepared.

[0035] Reaction Evaluation Reference Application Example 1 (the difference is that the Ba prepared in Example 1 2.0 -Bi4Ti3O 12 The catalyst was replaced by the catalyst prepared in this example of equal mass), and the hydrogen yield was 126.3 μmol g -1 h -1 Compared with comparative example 1, the hydrogen yield increased by about 5 times, indicating that TiO2 / ZnS-50 was successfully prepared.

[0036] Example 5

[0037] The ZnS / TiO2 heterojunction with a TiO2 nanorod mass fraction of 100% was obtained by the following process: First, 4.0mmol zinc chloride, 3.0mmol sodium chloride and TiO2 nanorods (anatase phase) with a ZnS mass fraction of 100% were added to 30mL isopropanol solution and stirred for 1.5h. Then, 8.0mmol thioacetamide was added and stirred for 1.5h and then transferred to a Teflon reactor lined with polytetrafluoroethylene, sealed and heat treated at 180℃ for 20h. After cooling to room temperature, the solid part was washed alternately with ethanol (25mL / time) and water (25mL / time) and centrifuged for 6 times. Finally, it was vacuum dried at 60℃ for 18h, cooled to room temperature, and ground to obtain a ZnS / TiO2 heterojunction nanomaterial with a TiO2 nanorod mass fraction of 100%, with a particle size of 10-100nm, marked as TiO2 / ZnS-100.

[0038] XRD test confirmed that the crystal phase of TiO2 in the prepared zinc sulfide / titanium dioxide nanorod heterojunction with a TiO2 mass fraction of 100% was anatase phase, and the crystal phase of ZnS was sphalerite phase, and the zinc sulfide / titanium dioxide heterojunction nanomaterial was successfully prepared.

[0039] Reaction Evaluation Reference Application Example 1 (the difference is that the Ba prepared in Example 1 2.0 -Bi4Ti3O 12 The catalyst was replaced by the catalyst prepared in this example of equal mass), and the hydrogen yield was 188.7 μmol g -1 h -1 , compared with comparative example 1, the hydrogen yield increased by about 7 times, indicating that TiO2 / ZnS-100 was successfully prepared.

[0040] Example 6

[0041] The ZnS / TiO2 heterojunction with a TiO2 nanotube mass fraction of 100% was obtained by the following process: First, 4.0mmol zinc chloride, 3.0mmol sodium chloride and TiO2 nanotubes with a ZnS mass fraction of 100% were added to 30mL aqueous solution and stirred for 1.5h. Then, 8.0mmol L-cysteine ​​amine was added and stirred for 1.5h and then transferred to a Teflon reactor lined with polytetrafluoroethylene, sealed and heat treated at 160℃ for 18h. After cooling to room temperature, the solid part was washed alternately with ethanol (25mL / time) and water (25mL / time) and centrifuged for 6 times. Finally, it was vacuum dried at 60℃ for 18h, cooled to room temperature, and ground to obtain a ZnS / TiO2 heterojunction nanomaterial with a TiO2 nanotube mass fraction of 100%, with a particle size of 10 to 100nm, marked as TiO2 / ZnS-100.

[0042] XRD test confirmed that the crystal phase of TiO2 in the prepared zinc sulfide / titanium dioxide nanotube heterojunction with a TiO2 mass fraction of 100% was anatase phase, and the crystal phase of ZnS was sphalerite phase, and the zinc sulfide / titanium dioxide heterojunction nanomaterial was successfully prepared.

[0043] Reaction Evaluation Reference Application Example 1 (the difference is that the Ba prepared in Example 1 2.0 -Bi4Ti3O 12 The catalyst was replaced by the catalyst prepared in this example of equal mass), and the hydrogen yield was 256.9 μmol g -1 h -1 , compared with comparative example 1, the hydrogen yield increased by about 10 times, indicating that TiO2 / ZnS-100 was successfully prepared.

[0044] Example 7

[0045] The ZnS / TiO2 nanosheet heterojunction with a ZnS mass fraction of 20% was obtained by the following process: First, 4.0mmol zinc chloride, 3.0mmol sodium chloride and TiO2 nanosheets with a ZnS mass fraction of 20% relative to TiO2 were added to 30mL ethanol solution and stirred for 0.5h. Then, 8.0mmol thioacetamide was added and stirred for 0.5h and then transferred to a Teflon reactor lined with polytetrafluoroethylene, sealed and heat treated at 160℃ for 20h. After cooling to room temperature, the solid part was washed alternately with ethanol (25mL / time) and water (25mL / time) and centrifuged for 6 times. Finally, it was vacuum dried at 60℃ for 18h, cooled to room temperature, and ground to obtain a ZnS / TiO2 nanosheet heterojunction nanomaterial with a ZnS mass fraction of 20%, with a particle size of 10-100nm, marked as ZnS / TiO2-20.

[0046] XRD test confirmed that the crystal phase of TiO2 in the prepared zinc sulfide / titanium dioxide nanosheet heterojunction with a TiO2 mass fraction of 20% was anatase phase, and the crystal phase of ZnS was sphalerite phase, and the zinc sulfide / titanium dioxide heterojunction nanomaterial was successfully prepared.

[0047] Reaction Evaluation Reference Application Example 1 (the difference is that the Ba prepared in Example 1 2.0 -Bi4Ti3O 12 The catalyst was replaced by the catalyst prepared in this example of equal mass), and the hydrogen yield was 137.8 μmol g -1 h -1 Compared with comparative example 1, the hydrogen yield increased by about 5 times, indicating that TiO2 / ZnS-20 was successfully prepared.

[0048] Example 8

[0049] The ZnS / TiO2 nanofiber heterojunction with a ZnS mass fraction of 5% was obtained by the following process: First, 4.0mmol zinc chloride, 3.0mmol sodium chloride and TiO2 nanofibers with a ZnS mass fraction of 5% relative to TiO2 were added to 30mL ethanol solution and stirred for 0.5h. Then, 8.0mmol thioacetamide was added and stirred for 0.5h and then transferred to a Teflon reactor lined with polytetrafluoroethylene, sealed and heat treated at 160℃ for 20h. After cooling to room temperature, the solid part was washed alternately with ethanol (25mL / time) and water (25mL / time) and centrifuged for 6 times. Finally, it was vacuum dried at 60℃ for 18h, cooled to room temperature, and ground to obtain a ZnS / TiO2 nanofiber heterojunction nanomaterial with a ZnS mass fraction of 5%, with a particle size of 10-100nm, marked as ZnS / TiO2-5.

[0050] XRD test confirmed that the crystal phase of TiO2 in the prepared zinc sulfide / titanium dioxide nanofiber heterojunction with a TiO2 mass fraction of 5% was anatase phase, and the crystal phase of ZnS was sphalerite phase, and the zinc sulfide / titanium dioxide heterojunction nanomaterial was successfully prepared.

[0051] Reaction Evaluation Reference Application Example 1 (the difference is that the Ba prepared in Example 1 2.0 -Bi4Ti3O 12 The catalyst was replaced by the catalyst prepared in this example of equal mass), and the hydrogen yield was 144.2 μmol g -1 h -1 , compared with comparative example 1, the hydrogen yield increased by about 5 times, indicating that TiO2 / ZnS-5 was successfully prepared.

[0052] Example 9

[0053] The zinc sulfide / titanium dioxide heterojunction with a TiO2 mass fraction of 20% was obtained by the following process: First, 4.0mmol zinc sulfate, 3.0mmol sodium chloride and TiO2 nanoparticles (anatase phase) with a ZnS mass fraction of 20% were added to 80mL aqueous solution and stirred for 0.5h. Then, 8.0mmol thioacetamide was added and stirred for 0.5h and then transferred to a Teflon reactor lined with polytetrafluoroethylene, sealed and heat treated at 160℃ for 20h. After cooling to room temperature, the solid part was washed alternately with ethanol (25mL / time) and water (25mL / time) and centrifuged for 6 times. Finally, it was vacuum dried at 60℃ for 18h, cooled to room temperature, and ground to obtain a zinc sulfide / titanium dioxide heterojunction nanomaterial with a TiO2 mass fraction of 20%, with a particle size of 10-100nm, marked as TiO2 / ZnS-20.

[0054] XRD test confirmed that the crystal phase of TiO2 in the prepared zinc sulfide / titanium dioxide heterojunction with a TiO2 mass fraction of 20% was anatase phase, and the crystal phase of ZnS was sphalerite phase, and the zinc sulfide / titanium dioxide heterojunction nanomaterial was successfully prepared.

[0055] Reaction Evaluation Reference Application Example 1 (the difference is that the Ba prepared in Example 1 2.0 -Bi4Ti3O 12 The catalyst was replaced by the catalyst prepared in this example of equal mass), and the hydrogen yield was 103.7 μmol g -1 h -1 , compared with comparative example 1, the hydrogen yield increased by about 4 times, indicating that TiO2 / ZnS-20 was successfully prepared.

[0056] Application Example 1

[0057] 10 mg of the TiO2 / ZnS-20 catalyst prepared in Example 1 was added to 1.0 ml of an aqueous solution containing 20% ​​methanol by volume. After removing oxygen from the system, an 18W ultraviolet LED lamp was turned on and the photocatalytic reaction was carried out for 4 hours under the condition of an ultraviolet light source of 365 nm. After the reaction, He was added as an internal standard to quantify the generated hydrogen. Gas chromatography analysis showed that the yield of hydrogen was 233.5 μmol g -1 h -1 .

[0058] Comparative Example 1

[0059] 10 mg of ZnS catalyst prepared in the same manner as in Example 1 but without the addition of TiO2 was added to 1.0 ml of a 20% methanol aqueous solution. After removing oxygen from the system, an 18W visible LED lamp was turned on and the photocatalytic reaction was carried out for 4 hours under the condition of a UV light source of 455 nm. After the reaction, He was added as an internal standard to quantify the generated hydrogen. Gas chromatography analysis showed that the yield of hydrogen was 25.9 μmol g -1 h -1 .

[0060] The results show that the effect of photocatalytic hydrogen production from water can be significantly improved by constructing a TiO2 / ZnS heterojunction structure. Compared with ZnS, the active hydrogen yield is increased by about 9 times. This shows that the TiO2 / ZnS heterojunction was successfully prepared, and the heterojunction structure significantly improves the activity of photocatalytic hydrogen production from water by promoting the separation of photogenerated carriers.

Claims

1. A method for preparing a zinc sulfide / titanium dioxide heterojunction nanomaterial, characterized in that The method comprises: (1) TiO2, zinc precursor, and (sodium chloride and / or potassium chloride) are stirred uniformly in a solvent, and then a sulfur precursor is added and stirred uniformly; (2) transferring the mixed slurry to a reactor for solvent thermal treatment; (3) After cooling, the solid part is washed with ethanol and water in sequence, separated by centrifugation, and dried to obtain zinc sulfide / titanium dioxide heterojunction nanomaterials.

2. The preparation method according to claim 1, characterized in that: In step (1), the TiO2 is in anatase phase and / or rutile phase; the morphology of TiO2 is one or more of controllably synthesized morphologies such as one-dimensional nanofibers, two-dimensional nanosheets and nanotubes, three-dimensional nanoparticles and nanorods; the zinc precursor is one or more of zinc sulfate, zinc nitrate and zinc chloride; the sulfur precursor is L-cysteine, thiourea and thioacetamide; and the solvent is one or more of ethanol, ethylene glycol and isopropanol.

3. The preparation method according to claim 1 or 2, characterized in that: In step (1), The molar ratio of the zinc precursor to the sulfur precursor is 1:1 to 1:5, preferably 1:1 to 1:2; the molar ratio of the zinc precursor to (the sum of sodium chloride and / or potassium chloride) is 4:1 to 1:1, preferably 2:1 to 4:3; The mass ratio of TiO2 to the zinc-based precursor to form ZnS is 0.001 to 1000:1, preferably 0.01 to 100:1; The ratio of the volume of the solvent to the mass of the materials (the sum of TiO2, zinc precursor, sulfur precursor, and sodium chloride and / or potassium chloride) is 10 to 50 mL / g, preferably 15 to 30 mL / g.

4. The preparation method according to claim 1, characterized in that: In step (1), the two stirring times are both 0.5 to 2 h, preferably 0.5 to 0.8 h.

5. The preparation method according to claim 1, characterized in that: In step (2), the solvent thermal treatment is carried out in a sealed reactor, the temperature of the solvent thermal treatment is 120-200° C., preferably 120-150° C.; the time of the solvent thermal treatment is 12-48 hours, preferably 16-24 hours.

6. The preparation method according to claim 1, characterized in that: In step (3), the amount of ethanol and water used to alternately wash the solid part is 200-800 mg solid / 25 mL (ethanol or water), for a total of 3-8 times; The vacuum drying temperature is 60 to 100° C., preferably 70 to 80° C.; the drying time is 12 to 36 hours, preferably 18 to 24 hours.

7. A zinc sulfide / titanium dioxide heterojunction nanomaterial prepared by the preparation method according to any one of claims 1 to 6.

8. Use of the zinc sulfide / titanium dioxide heterojunction nanomaterial according to claim 7 in a process of catalytic photolysis of water to produce hydrogen.